When the river runs dry: human and ecological values of dry riverbeds. Issue 4 (29th March 2012) - Steward, Alisha L; von Schiller, Daniel; Tockner, Klement; Marshall, Jonathan C; Bunn, Stuart E
Abstract : Temporary rivers and streams that naturally cease to flow and dry up can be found on every continent. Many other water courses that were once perennial now also have temporary flow regimes due to the effects of water extraction for human use or as a result of changes in land use and climate. The dry beds of these temporary rivers are an integral part of river landscapes. We discuss their importance in human culture and their unique diversity of aquatic, amphibious, and terrestrial biota. We also describe their role as seed and egg banks for aquatic biota, as dispersal corridors and temporal ecotones linking wet and dry phases, and as sites for the storage and processing of organic matter and nutrients. In light of these valuable functions, dry riverbeds need to be fully integrated into river management policies and monitoring programs. We also identify key knowledge gaps and suggest research questions concerning the values of dry riverbeds.